2011
DOI: 10.1093/infdis/jir134
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of CRP, D-dimer, IL-6, and Hyaluronic Acid Before Initiation of Antiretroviral Therapy (ART) Are Associated With Increased Risk of AIDS or Death

Abstract: Biomarkers of Inflammation (CRP, IL-6), coagulation (D-dimer), and tissue fibrosis (HA) measured pre-ART and at 1 month are associated with higher risk of AIDS events, IRIS, or death, warranting additional study as risk stratification strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
252
5
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 280 publications
(288 citation statements)
references
References 36 publications
23
252
5
4
Order By: Relevance
“…Moreover, high level of CRP was a risk factor of IRIS. 15 These results were inconsistent with our findings. Therefore, if increased levels of CRP, ESR and LDH are found in HIV/TB co-infected patients, some features including the duration of HAART treatment, clinical symptoms, CD4 + cell counts and HIV RNA loads should be considered along with the infection to comprehensively evaluate the possibility of developing IRIS and to help make the most appropriate early treatment strategy.…”
Section: Discussioncontrasting
confidence: 95%
“…Moreover, high level of CRP was a risk factor of IRIS. 15 These results were inconsistent with our findings. Therefore, if increased levels of CRP, ESR and LDH are found in HIV/TB co-infected patients, some features including the duration of HAART treatment, clinical symptoms, CD4 + cell counts and HIV RNA loads should be considered along with the infection to comprehensively evaluate the possibility of developing IRIS and to help make the most appropriate early treatment strategy.…”
Section: Discussioncontrasting
confidence: 95%
“…3,4 Meanwhile, three types of arguments have emerged to support even earlier initiation of ART. First, there is increasing documentation of inflammation in people with uncontrolled viral replication and of non-acquired immunodeficiency syndrome (AIDS)-defining noninfectious diseases as causes of death in HIV-infected persons 5,6 (with AIDS-defining diseases identified as diseases included in the Centers for Disease Control and Prevention case definition of AIDS 7 ). Second, among patients living with HIV in lower-resource countries, the rates of tuberculosis and bacterial diseases are high.…”
mentioning
confidence: 99%
“…The higher secretion of IL-6, which is considered an activator of the acute phase responses [27] and also a marker of critical illness during influenza infection [28,5], may also explain the more severe clinical outcomes reported in HIV-negative patients, supporting the hypothesis that clinical complications following influenza infection may result from an inflammatory burst. It was shown that higher levels of IL-6 in pre-HAART HIV patients correlate with higher morbidity and mortality rates [29]. These data suggest that IL-6 can effectively be considered as a valuable marker of severe infection.…”
Section: Discussionmentioning
confidence: 92%